Association of Dietary Carrot Intake With Bladder Cancer Risk in a Prospective Cohort of 99,650 Individuals With 12.5 Years of Follow-Up - Xu, Xin; Zhu, Yi; Ye, Sunyi; Li, Shiqi; Xie, Bo; Meng, Hongzhou; Wang, Shuo; Xia, Dan (Frontiers in Nutrition, 2021)
Previous studies have provided limited evidence for the effect of carrot intake on bladder cancer incidence. This study aimed to evaluate the association between carrot consumption and bladder cancer risk in the Prostate, Lung, Colorectal, and Ovarian Cancer (PLCO) Screening cohort. PLCO enrolled 154,897 participants between November 1993 and July 2001 from 10 clinical screening centers throughout the United States. Hazard ratios (HRs) and 95% confidence intervals (CIs) were estimated using Cox regression model adjusting for confounders. A meta-analysis was also performed based on all available prospective studies with DerSimonian and Laird random-effects model to calculate summary relative risk (RR) and 95% CI. After a median of 12.5 years of follow-up, 762 incident bladder cancer cases occurred. We found no statistically significant association between dietary carrot intake and bladder cancer risk. The multivariate-adjusted HR of bladder cancer for participants in the highest category of total carrot intake compared with those in the lowest category was 0.96 (95% CI: 0.76-1.22; P for trend = 0.436). Corresponding adjusted HR was 0.98 (95% CI 0.90-1.06) per 1 SD increment of carrot intake. A meta-analysis based on two previous cohort studies and our study also found no significant association between carrot intake and bladder cancer risk (Summary HR 1.02, 95% CI 0.95-1.10) without obvious heterogeneity between studies (P = 0.859, I2 = 0.0%). In summary, analysis of the PLCO cohort did not provide evidence that dietary consumption of carrot was associated with the risk of bladder cancer.